Perancangan Sistem Perencanaan Konten Media Sosial Berbasis Web Terintegrasi Artificial Intelligence (AI) Bagi UMKM Menggunakan Framework Next.js dengan Model Prototype - Nasrullah Gunawan; Muhammad Irwan Padli Nasution (JUSIFOR : Jurnal Sistem Informasi dan Informatika, 2025)
Digital marketing through social media is crucial for the sustainability of MSMEs, yet many business owners face challenges such as inconsistent schedules, difficulty finding content ideas, and limited time for drafting captions. The purpose of this study is to create a web-based social media content planning system utilizing AI to help MSMEs manage their marketing better. The system development method used is the Software Development Life Cycle (SDLC) with the Prototype model, comprising requirement gathering, quick design, prototype building, and user evaluation phases. The system utilizes the Next.js framework, TailwindCSS, and Supabase, along with the IBM Granite Instruct AI model for automated caption features. The results produced a system design featuring an interactive content calendar, publication status management, and an AI assistant. Evaluations indicate the system is proven effective in organizing content planning. Development of automated publishing features, multi-user collaboration support, and deeper content performance analytics are recommended for future research stages.